Followers Work Engagement Under The Shadow of Narcissism: With Resilience as The Moderating - Renatta Fayza Alam; Siti Nuzulia (Journal of Educational, Health and Community Psychology, 2026)
Employee work engagement in Indonesia remains relatively low. One of the factors that may contribute to this issue is associated from their leaders, particularly how their personality is perceived by followers. This study examined the linked of perceived narcissistic admiration and narcissistic rivalry on follower work engagement within a collectivist culture, with resilience as a moderating variable. Addressing the gap in distinguishing between these two dimensions of narcissism, this research aimed to understand their differential effects on employee engagement. Data were collected from 246 active employees using a cross-sectional design and analyzed using the General Linear Model. The results indicated that narcissistic rivalry significantly linked negatively to work engagement. Counterintuitively, higher levels of follower resilience amplified this negative effect, resulting in a steeper decline in engagement under antagonistic conditions. In contrast, narcissistic admiration did not show a significant effect on work engagement. These findings suggest that resilience does not consistently function as a protective buffer in unsupportive environments. The study highlights the importance of minimizing antagonistic interpersonal dynamics to sustain work engagement and relational harmony.